DETERMINATION OF RISK MINIMIZATION STRATEGY FOR HERBAL DRINK PRODUCTION WITH GMP APPROACH USING SCORING AND AHP - Ratining Indah Wardani; Imam Santoso; Riska Septifani (Jurnal Teknologi Pertanian, 2022)
Herbal drinks such as herbs have become part of the culture in Indonesia. The herbal plants processed into herbal drinks include bilimbi fruit (Averrhoa bilimbi L.) and secang (Caesalpinia sappan L.). This study aims to determine the risk minimization strategy in producing herbal drinks in CV XYZ by analyzing 14 aspects of Good Manufacturing Practices (GMP) using a scoring form and the Analytical Hierarchy Process (AHP) method. The scope of GMP in this study orients to how to produce good processed food. Determination of risk minimization strategy using the Analytical Hierarchy Process (AHP) method. The assessment results in applying GMP in CV XYZ using scoring calculation gotten three aspects with the highest deviation, “the sufficient qualify category", i. e. the building aspect (78.39%), storing (78.47%), and controlling (78.65%). These results as the base for arranging the risk minimization strategy with some criteria and alternatives using AHP calculation. The priority criteria for risk minimization strategies are the effectiveness level (0.608), the easiness of applying (0.313), and cost (0.079). Then, three priorities of alternative risk minimization for CV XYZ based on the global weight are the repairing of ventilation design (0.323) by adding ventilation in the production room, screens for dust filters that can be easily removed, final product storage separation (0.228) by placing materials or products that have a strong odor and have the potential to affect the final product in a separate room, making SOPs for the production process (0.209).